Evaluating the Use of Commercially Available Wearable Wristbands to Capture Adolescents' Daily Sleep Duration. (1st October 2019) - George, Madeleine J.; Rivenbark, Joshua G.; Russell, Michael A.; Ng'eno, Leonard; Hoyle, Rick H.; Odgers, Candice L.
Abstract : Commercially available wearable devices are marketed as a means of objectively capturing daily sleep easily and inexpensively outside of the laboratory. Two ecological momentary assessment studies—with 120 older adolescents (aged 18–19) and 395 younger adolescents (aged 10–16)—captured nightly self‐reported and wearable (Jawbone) recorded sleep duration. Self‐reported and wearable recorded daily sleep duration were moderately correlated ( r  ~ .50), associations which were stronger on weekdays and among young adolescent boys. Older adolescents self‐reported sleep duration closely corresponded with estimates from the wearable device, but younger adolescents reported having an hour more of sleep, on average, compared to device estimates. Self‐reported, but not wearable‐recorded, sleep duration and quality were consistently associated with daily well‐being measures. Suggestions for the integration of commercially available wearable devices into future daily research with adolescents are provided.